Investigating correlated fluctuations of conserved charges with net-[lambda] fluctuations in Pb-Pb collisions at ALICE - Ohlson, Alice (Nuclear physics. A, Nuclear and hadronic physics, 2019)
Event-by-event fluctuations of conserved charges - such as electric charge, strangeness, and baryon number - in ultrarelativistic heavy-ion collisions provide insight into the properties of the quark-gluon plasma and the QCD phase diagram. They can be related to the higher moments of the multiplicity distributions of identified particles, such as the Λ baryon which carries both strangeness and baryon number and is thus of particular interest. We present the first measurement of net-Λ fluctuations in Pb-Pb collisions at sNN=5.02TeV as a function of centrality and the pseudorapidity acceptance of the measurement. The results are compared to expectations of the effects of global baryon number conservation as well as to predictions from the HIJING Monte Carlo event generator. In this analysis the Identity Method is applied in a novel way to account for the combinatoric background in the invariant mass distribution.